Allelopathy? I don’t know! I've never seen! I only hear about it! (Research, Society and Development, 2020)
Allelopathy is defined by the International Society of Allelopathy as the science that studies any process involving essentially the secondary metabolites produced by plants, algae, bacteria and fungi which influence the growth and development of agricultural and biological systems, including positive and negative effects. However, several doubts are evident in new researchers of the area, such as the emergence and evolution of this science. In this way, we didactically gather some important information about allelopathy, which are distributed in (1) Allelopathy: History and Definitions, (2) Mode of Action of Allelochemicals and (3) Chemical Nature of Allelochemicals, in order to guide the new researchers and enable the use of this information in the classroom as a theoretical resource.